XAB2 tagSNPs contribute to non-small cell lung cancer susceptibility in Chinese population - Pei, Na (BMC Cancer, 2015)
BACKGROUND: XPA-binding protein 2 (XAB2) interacts with Cockayne syndrome complementation group A (CSA), group B (CSB) and RNA polymerase II to initiate nucleotide excision repair. This study aims to evaluate the association of XAB2 genetic variants with the risk of non-small cell lung cancer (NSCLC) using a tagging approach. METHODS: A hospital-based case-control study was conducted in 470 patients with NSCLC and 470 controls in Chinese population. Totally, 5 tag single nucleotide polymorphisms (SNPs) in XAB2 gene were selected by Haploview software using Hapmap database. Genotyping was performed using iPlex Gold Genotyping Asssy and Sequenom MassArray. Unconditional logistic regression was conducted to estimate odd ratios (ORs) and 95 % confidence intervals (95 % CI). RESULTS: Unconditional logistic regression analysis showed that the XAB2 genotype with rs794078 AA or at least one rs4134816 C allele were associated with the decreased risk of NSCLC with OR (95 % CI) of 0.12 (0.03–0.54) and 0.46 (0.26–0.84). When stratified by gender, we found that the subjects carrying rs4134816 CC or CT genotype had a decreased risk for developing NSCLC among males with OR (95 % CI) of 0.39 (0.18–0.82), but not among females. In age stratification analysis, we found that younger subjects (age ≤ 60) with at least one C allele had a decreased risk of NSCLC with OR (95 % CI) of 0.35 (0.17–0.74), but older subjects didn’t. We didn’t find that XAB2 4134816 C > T variant effect on the risk of NSCLC when stratified by smoking status. The environmental factors, such as age, sex and smoking had no effect on the risk of NSCLC related to XAB2 genotypes at other polymorphic sites. CONCLUSIONS: The XAB2 tagSNPs (rs794078 and rs4134816) were significantly associated with the risk of NSCLC in Chinese population, which supports the XAB2 plays a significant role in the development of NSCLC.